The Importance of Positive Externalities and Intersectoral Linkages in Determining Growth Path of Developing Economies - Deden Dinar Iskandar (Jurnal Ekonomi dan Studi Pembangunan, 2009)
This paper is intended to explore the significance of intersectoral linkage in determining the growth path of developing economies. It is commonly believed that intersectoral linkages among firms and industries is importance since it provides the positive externalities that enables firms or industries to gain the increasing return to scale. Increasing return to scale is the characteristic that drives the process of growth. The paper describes the source of increasing return to scale, the relation between externalities and sectoral linkages, and the link between sectoral linkages and growth path in developing economies. The analysis of the paper is based on the literatures review. All the models reviewed suggest the importance of sectoral linkages from various points of view, and come to the similar conclusion that the weak or absence of sectoral linkages could lead developing economies to be trapped in low equilibrium economy and low growth path. The conclusion is how the government able to release the developing economies from the historical trap of low equilibrium economy and low growth path by establishing a rational policy.Keywords: increasing return to scale, externalities, sectoral linkages, growth path